A best-practice model for integrating interdisciplinarity into the higher education student experience. Issue 3 (4th March 2019) - Power, E. J.; Handley, J.
ABSTRACT: Today's global society creates an environment characterised by complex problems, solutions to which require transcendence of traditional discipline-based boundaries, and new forms of knowledge-sharing. Higher education (HE) has a central role in interdisciplinary knowledge creation and dissemination, reinforced by funding councils, professional bodies and government policy. That notwithstanding, there is currently no recognised best practice approach to interdisciplinary working in UK HE institutes. The aim of this paper is to develop a best practice model to facilitate interdisciplinarity within the UK HE sector, focusing on teaching and learning and the student learning experience. Based on the results of an exploratory and empirical enquiry, a HE Interdisciplinary Model (HIM) of best practice is proposed. The HIM is informed by the development of four themes and six ensuing enablers from a synthesis of perceived barriers, possible facilitators and potential solutions to interdisciplinarity within UK HE. However, further research is necessary to validate the proposed model.